IMPACT OF EARLY MARRIAGE IN CIKANDE DISTRICT: IMPACT OF EARLY MARRIAGE CASE STUDY ON THREE PEOPLE WHO EXPERIENCED EARLY MARRIAGE IN CIKANDE DISTRICT - Siti Khaeriyah; Evi Afiati; Alfiandy Warih Handoyo (Study Program Guidance and Counseling, Univesitas Pendidik, 2021)
This research departs from the rise of early marriage in Indonesia, especially in the Cikande District. Early marriage is still ongoing, this is certainly a worrying issue for all of us. Those who marry at this age are teenagers, where this phase is a determinant for adult life. This research is to find out how the impact and trigger factors for early marriage in Cikande District. This research uses qualitative case studies, while this research will try to describe three cases of early marriage in the Cikande. Research data is obtained through interviews, observation, and documentation, this is done to provide a complete explanation of the research questions. To illustrate this, this study uses Hurlock's theory of adolescent developmental phases, where this theory will help describe adolescent development, and then describe the impact and triggering factors of early marriage in the Cikande. From this study, there are several findings, that the impact of early marriage in the Cikande District is on dropping out of high school, then, the triggering factor for this marriage is the lack of knowledge about early marriage, which can have a domino effect on every aspect of life. teenager. For this reason, in this education section, researchers assess that Guidance and Counseling studies can play a role in the public sphere or people's lives, not only in the classroom.